Spoilage association of chicken skin. - Daud, H B (1979)
The bacterial succession on the skin of broiler chicken carcasses stored at 2 degrees C was traced, and the ability of representative isolates to produce off-odors was determined by using sterile leg and breast muscle sections. Off-odors were identified by olfactory and chemical means. The inability of peptone-iron agar to detect sulfide-producing strains was noted.